Impacts of Singapore Formula One Grand Prix : a perspective from local residents. - Lin, Hermes Yichao. (2009)
Successful large-scale events can help in promoting tourism and economic activity in a country, and the impacts brought by these events are felt by both the industry players and locals. This report attempts to investigate and identify the factors that constitute success for the Singtel Formula One (F1) Grand Prix Night Race event held in Singapore and offers recommendations to the organizers to improve on areas perceived as crucial to making an event similar to this successful. The survey results collated provided an insight into the perceptions of the Singaporean population about the F1 event. The general consensus was that the event was, by and large, a successful one, although not without some shortfalls in terms of service quality and prices. Moreover, the survey findings also showed that the benefits resulting from the F1 event were believed to outweigh the costs it entailed, notwithstanding some disturbances to the daily routines of Singaporeans, with respect to traffic and noise issues. The recommendations offered in this report are targeted at the areas which have been identified in the survey as having dampening effects on the impression of the F1 event. By channelling efforts to minimise these areas of concern, the end result would be an improvement to subsequent events. Recommendations tackle the major issues of traffic and prices.